Rencana Bisnis Kuliner Bebek Blengong di Jakarta - Suwandi, Suwandi; Purwantono, Imam (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
The Blengong duck culinary business "LNYBW" is a business plan that had ever been established in Wisma Bakrie, South Jakarta; with a healthy and fast food proposition, as well as the main activity of providing Blengong duck food menu using food truck outlets for employees and families consisting of various meal packages made from Blengong duck. The method that used is descriptive analysis was compiled based on information obtained from field surveys and business models made based on information from duck culinary business players, mainly located in Jakarta and Brebes, with instruments Empathy Map & Business Model Canvas. Assessing the feasibility of the Blengong duck culinary business plan is carried out with financial analysis parameters, payback period, NPV, and IRR. The results of the analysis and discussion of the study concluded that: 1) The Blengong duck food menu is healthy food that low cholesterol; 2) financially, the capital needed is not too high at IDR 60 million, in business feasibility, the projection of financial flows for three years shows a 1-year payback period, also positive NPV, and IRR  which is greater than  deposit interest in commercial bank.